Taxation of electronic commerce and digital business in the conditions of global convergence economics - Kraus, Kateryna; Kraus, Nataliia (Business, Management and Economics Engineering, 2025)
Purpose – Identify the relationship between the amount of taxes and their payment by a digital enterprise and develop recommendations for improving the quality of e- commerce taxation.Research methodology – On the basis of dialectical and systematic methods, the influence of the amount of the tax on filling the budgets of countries and the expansion of digital activities of enterprises was investigated. The spatial set of the study is economic agents of the EU and the USA who use the Internet for their business activities. The possibilities of conducting e- business in 15 countries of the world were studied. The time frame of the study is 2015–2025. Findings – The tax on digital products/services and virtual business is characterized through the prism of the amount of the tax, the procedure for its collection, and the amount of revenue to the budgets.Research limitations – The limitation of the study is that not all countries of the world that carry out e-commerce or engage in digital business have an open and regulated policy of taxation.Practical implications – The content of practical advice, the use of which will make it possible to maintain positive dynamics in the taxation of digital entrepreneurship, has been revealed.Originality/Value – After analyzing the graphical interpretation of the Laffer curve for digital entrepreneurship, we managed to find out that higher tax rates restrain the economic activity of digital enterprises.